Peran Logo Bakmi Hotplate Serang dalam Membangun Identitas Merek - Tafana Destiana Larassetya; Arfian Suryasuciramdhan; Febriya Alinda Rahayu; Alisya Safira; Muhammad Salim Al Bana (Lembaga Pengembangan Kinerja Dosen, 2025)
. Logo is a visual element that has an important role in shaping brand identity, especially in micro, small and medium enterprises (MSMEs) in the culinary field. This research aims to analyze the role of Bakmi Hotplate Serang's logo in building brand identity through a descriptive qualitative approach. Data was collected through observation, visual documentation, and interviews with business owners and customers. The results show that the logo of Bakmi Hotplate Serang not only functions as a symbol of identity, but also a visual communication tool that conveys brand values and characteristics to consumers. With a simple yet meaningful design, the logo is able to create a warm, distinctive, and recognizable impression. Its consistent use in various promotional media strengthens the brand image and increases customer trust. This research confirms the importance of visual elements in MSME branding strategies as an effective form of communication in the midst of market competition.